On the Relation between Blade Loading and In-Passage Energy Balance - Yinbo Mao (MDPI AG, 2021)
This paper presents a novel theory regarding the blade loading and the passage flow field within general turbomachineries. The basic philosophy is to establish an analytical relation between the loading, the flow angle, and the blade geometry based on the conservation of energy. Detailed validations and analyses will be carried out to provide a general scope regarding the theory itself as well as its advantages and limitations in common applications. The paper includes the theoretical derivation of the target relation. The starting point is the standard RANS equations. From that, with the aid of the passage-average operator, the relation between the loading and the passage flow field is derived under the energy balance. Theoretical analyses regarding the validity of the relation are performed based on the simulation results and test data on different cascades. Discussions are conducted regarding the assumption and potential applications of the theory. Conclusions are drawn on the applicability of the theory to introduce its potential applications in general turbomachineries.